Simulation of viscoelastic flows of polymer solutions in abrupt contractions using an arbitrary lagrangian eulerian (ALE) based finite element method - Ganvir, Vivek; Lele, Ashish K.; Thaokar, Rochish; Gautham, Basavarsu P. (Journal of Non-Newtonian Fluid Mechanics, 2007)
We present a method for simulation of viscoelastic flows using an Arbitrary Lagrangian Eulerian (ALE) technique based finite element formulation. The ALE technique provides advantages of both Lagrangian and Eulerian frameworks by allowing the computational mesh to move in an arbitrary manner, independent of the material motion. In the present method, a fractional step ALE technique is employed in which the Lagrangian phase of material motion and convection arising out of mesh motion are decoupled. In the first step the relevant flow and constitutive equations are solved in Lagrangian framework. The simpler representation of polymer constitutive equations in a Lagrangian framework avoids the difficulties associated with convective terms thereby resulting in a robust numerical formulation. In the second step the mesh is moved in ALE mode and the associated convection of the stress is performed using a Godunov type scheme. This ALE technique is easy to implement and can accurately simulate the complex viscoelastic behaviour of transient polymer flow through complex geometries. In the present study, steady flows through abrupt contractions of planar and axisymmetric geometries are studied by performing transient flow simulations until steady state is achieved. The proposed method is validated with previously published numerical and experimental studies for polymer solutions obeying the Oldroyd B and Phan Thien Tanner (PTT) models. The simulated corner and lip vortex enhancement mechanism and flow behavior are in good agreement with experimentally obtained flow visualization photographs. The strength of the proposed method lies in its ability to simulate free surface flows such as swell. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: abrupt contraction; Arbitrary Lagrangian Eulerian; finite element; simulations

Prediction of extrudate swell in polymer melt extrusion using an Arbitrary Lagrangian Eulerian (ALE) based finite element method - Ganvir, Vivek; Lele, Ashish K.; Thaokar, Rochish; Gautham, Basavarsu P. (Journal of Non-Newtonian Fluid Mechanics, 2009)
Accurate prediction of extrudate (die) swell in polymer melt extrusion is important as this helps in appropriate die design for profile extrusion applications. Extrudate swell prediction has shown significant difficulties due to two key reasons. The first is the appropriate representation of the constitutive behavior of the polymer melt. The second is regarding the simulation of the free surface, which requires special techniques in the traditionally used Eulerian framework. In this paper we propose a method for simulation of extrudate swell using an Arbitrary Lagrangian Eulerian (ALE) technique based finite element formulation. The ALE technique provides advantages of both Lagrangian and Eulerian frameworks by allowing the computational mesh to move in an arbitrary manner, independent of the material motion. In the present method, a fractional-step ALE technique is employed in which the Lagrangian phase of material motion and convection arising out of mesh motion are decoupled. In the first step, the relevant flow and constitutive equations are solved in Lagrangian framework. The simpler representation of polymer constitutive equations in a Lagrangian framework avoids the difficulties associated with convective terms thereby resulting in a robust numerical formulation besides allowing for natural evolution of the free surface with the flow. In the second step, mesh is moved in ALE mode and the associated convection of the variables due to relative motion of the mesh is performed using a Godunov type scheme. While the mesh is fixed in space in the die region, the nodal points of the mesh on the extrudate free surface are allowed to move normal to flow direction with special rules to facilitate the simulation of swell. A differential exponential Phan Thien Tanner (PTT) model is used to represent the constitutive behavior of the melt. Using this method we simulate extrudate swell in planar and axisymmetric extrusion with abrupt contraction ahead of the die exit. This geometry allows the extrudate to have significant memory for shorter die lengths and acts as a good test for swell predictions. We demonstrate that our predictions of extrudate swell match well with reported experimental and numerical simulations. (c) 2008 Elsevier BY. All rights reserved.
Keywords: Arbitrary Lagrangian Eulerian; Extrudate (die) swell; Free surface simulations

Extrudate swell of linear and branched polyethylenes: ALE simulations and comparison with experiments - Ganvir, Vivek; Gautham, Basavarsu P.; Pol, Harshawardhan; Bhamla, M. Saad; Sclesi, Lino; Thaokar, Rochish; Lele, Ashish K.; Mackley, Malcolm (Journal of Non-Newtonian Fluid Mechanics, 2011)
Extrudate swell is a common phenomenon observed in the polymer extrusion industry. Accurate prediction of the dimensions of an extrudate is important for appropriate design of dies for profile extrusion applications. Prediction of extrudate swell has been challenging due to (i) difficulties associated with accurate representation of the constitutive behavior of polymer melts, and (ii) difficulties associated with the simulation of free surfaces, which requires special techniques in the traditionally used Eulerian framework. In a previous work we had argued that an Arbitrary Lagrangian Eulerian (ALE) based finite element formulation may have advantages in simulating free surface deformations such as in extrudate swell. In the present work we reinforce this argument by comparing our ALE simulations with experimental data on the extrudate swell of commercial grades of linear polyethylene (LLDPE) and branched polyethylene (LOPE). Rheological behavior of the polymers was characterized in shear and uniaxial extensional deformations, and the data was modeled using either the Phan-Thien Tanner (PTT) model or the eXtended Pom-Pom (XPP) model. Additionally, flow birefringence and pressure drop measurements were done using a 10:1 contraction-expansion (CE) slit geometry in a MultiPass Rheometer. Simulated pressure drop and contours of the principal stress difference were compared with experimental data and were found to match well. This provided an independent test for the accuracy of the ALE code and the constitutive equations for simulating a processing-like flow. The polymers were extruded from long (L/D=30) and short (L/D=10) capillaries dies at 190 degrees C. ALE simulations were performed for the same extrusion conditions and the simulated extrudate swell showed good agreement with the experimental data. Crown Copyright (C) 2010 Published by Elsevier B.V. All rights reserved.
Keywords: ALE-FEM; extrudate swell; Flow birefringence; MultiPass Rheometer; PSD; PTT; XPP

Numerical and experimental studies on extrudate swell of branched polyethylene through axisymmetric and planar dies - Ganvir, Vivek; Gautham, Basavarsu P.; Thaokar, Rochish; Lele, Ashish K.; Pol, Harshwardhan (Journal of Polymer Engineering, 2011)
Extrudate swell is simulated using an Arbitrary Lagrangian Eulerian (ALE) technique based finite element formulation and the same has been validated by comparing the results with reported numerical and experimental studies. In the present work we compare our ALE simulations with our own experimental data on the extrudate swell of commercial grade low density polyethylene (LDPE) resin. The resins were characterized for their rheological behavior in both shear and uniaxial extension. The polymers were extruded from a capillary under isothermal conditions and the extrudates were observed on-line using a video camera. ALE simulations were performed using molecular constitutive model like eXtended Pom-Pom (XPP) for branched (LDPE). The simulated extrudate swell was a good match with the experimental data. It was found that the swell values of LPDE through planar die are higher than the axisymmetric die.
Keywords: ALE-FEM; extrudate swell; polymer flow simulations; XPP

Synthesis of N-oxyethylene substituted imidazolium-based zwitterions as a recyclable solvent for cellulose dissolution - Jadhav, Sachin; Ganvir, Vivek; Singh, Madan Kumar; Shanmuganathan, Kadhiravan (Cellulose, 2023)
Cellulose is a readily available, renewable, and natural biomaterial that has the potential to replace synthetic fibres. However, their processing to shaped materials such as fibre or film is still complex and restricted due to its insolubility in most conventional solvents. Herein, we present the synthesis and cellulose dissolution characteristics of a new class of recyclable zwitterions composed of tethered N-oxyethylene substituted imidazolium cation and alkyl carboxylate anion. Investigations on cellulose dissolution showed that increasing the alkyl chain length of carboxylate anion and introduction of oxyethylene unit on imidazolium ring led to better cellulose dissolution ability, and up to 12% (w/w) cellulose could be dissolved in aqueous zwitterions at 105 degrees C. The thermal behavior of zwitterions and their cellulose solutions was characterized by TGA and found to be more stable than the NMMO and Lyocell solutions. Rheological characterization of cellulose solutions revealed viscoelastic behavior and zero shear viscosity of 6-12% (w/w) cellulose solution in hexanoate containing aqueous zwitterion was 555 to 5900 Pa.s at 120 degrees C. The characteristics of cellulose solution indicate its potential for processing to cellulose fibre by extrusion through a tiny spinneret. Physico-chemical analysis of regenerated cellulose indicates that zwitterions cause no adverse effect on cellulose structure and morphology during dissolution. The zwitterions are recovered after the cellulose regeneration process, and the recovery was found to be 99.6% after purification using the ion-exchange method.
Keywords: Carboxylate anion; Cellulose dissolution; Oxyethylene unit; Regenerated cellulose; Rheology; zwitterions

Structure and properties of the cellulose fibres spun from imidazolium-based carboxylate functionalized zwitterionic liquid - Jadhav, Sachin; Singh, Dhirendra; Gupta, Deepika; Ganvir, Vivek; Singh, Madan Kumar; Shanmuganathan, Kadhiravan (CARBOHYDRATE POLYMERS, 2025)
Keywords: cellulose; Direct dissolution; Zwitterionic liquid